Impact of Using Recycled Raw Material on Sustainability at a Packaging Manufacturer - ALJOUJA, OMAR (İstanbul Kültür Üniversitesi, 2024)
Sustainability is a crucial aspect of earth's ecosystem, making sure resources are available for the next generation, while reducing the possibility of climate change, it's an ethical and obligation responsibility for all decision makers across the world, it encourages accountable recourse usage, economic stability, and social equality, encouraging a balance between humans and nature which is essential for a long-term health and well-being of earth. This study begins by preparing a questionnaire that included economic, environmental, and social sustainability inquiries and presenting it to a recyclable packaging manufacturer that uses different concentrations of recyclable raw material and measuring the impact it had on the three pyramids of sustainability within that company, the questionnaire results were gathered and analyzed using Excel and GAMS programs. The results showed that a 12% change in recyclable raw material concentrations had direct and indirect effects on all three sustainability factors, where it had a 13% increase on the environmental factors, a 6% increase on the economic factors and a 5.4% impact on the social factors. In conclusion, utilizing higher grade recyclable materials will yield better environmental, economic, and social outcomes. However, it is important to acknowledge that limitations do exist such as market dynamics, overall budget, and technological constraints.
Bı̇r Ambalaj Üretı̇cı̇sı̇nde Gerı̇ Dönüştürülmüş Hammadde Kullanımının Sürdürülebı̇lı̇rlı̇k Üzerı̇ndekı̇ Etkı̇sı̇
Yüksek lisans tezi.
Keywords: Sustainability; Recyclability